Evaluate the drivers for digital transformation in higher education institutions in the era of Industry 4.0 based on decision-making method - Kunqi Wang; Bangxi Li; Tian Tian; Norhayati Zakuan; Pratibha Rani (Journal of Innovation & Knowledge (JIK), 2023)
The digitalization of higher education (HE) institutions and relevant issues have attracted the attention of many educational stakeholders. ICT has become a subject of high importance in every context, particularly in the workplace; thus, a principal goal for universities and schools is to prepare future professionals capable of dealing with problems and searching for effective solutions by their digital competence as a key skill. In this regard, a new framework is developed to evaluate the main drivers of digital transformation in higher education institutions (HEIs) in the era of industry 4.0. The developed framework is proposed a decision approach that can effectively use the presented information to make decisions of high rationality. This framework is applied to compute the subjective and objective criteria weights, and it is used to assess the preferences of organizations. An empirical case study to evaluate the main drivers for the implementation of digital transformation in HEIs is taken. According to the findings, the most significant drivers for the implementation of digital transformation in HEIs in the era of Industry 4.0 are developing, updating, and adapting a curriculum (0.0425), integration of digital technologies for universal education (0.0420), and cloud computing (0.0419), respectively. Hence, the evaluation results also show that the option higher education institution (HEI)-4 has the highest overall utility degree (1.845) over different drivers for the implementation of digital transformation in HEIs in the era of Industry 4.0. Also, comparison and sensitivity investigation are made to show the superiority of the developed framework.
Keywords: A2; O33; O32; Q55; C44; D81; L86; 650; Decision making; Digital transformation; Education 4.0; Higher education institutions; Industry 4.0